ROLE OF GOVERNMENT SCHEMES IN THE SOCIAL AND ECONOMIC UPLIFTMENT OF TRIBAL COMMUNITIES - Jaiman, Chandrashekhar; Kanwar, Santosh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India is a vast country. Many cultures are found here. Many castes and tribes live in this country with diverse cultural and social structure. The total population of scheduled tribe community in India is about 8.6%, these communities mainly live in forests, mountains and border areas. Due to this reason, they are very backward in social, educational and economic terms. They are not able to develop fully. These tribes form a special community, whose contribution has not only been in nature conservation, but they have also been the carriers of traditional knowledge, tribal art and culture and values. But reasons like historical exploitation, lack of education and health services, geographical location etc. have brought them to a state of backwardness. Keeping in mind the needs of the tribals, many welfare schemes and programmes are being run by the Central and State Government for their overall development. These are based on education, health, economic development and skill development. The objective of tribal development is to bring them into the mainstream, empower them and protect their traditional rights. Every scheme, whether it is in the field of education or health, will be successful only when the local people are familiar with their need, utility and process. It has been observed in many tribal areas that tribal development schemes are not very successful because their structure is not very simple and clear. Due to this, these schemes are beyond the understanding of the tribal community.